The effect of 1,25-dihydroxyvitamin D3 on MSX2 gene expression during tooth and alveolar bone development - Intan Ruspita (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: 1,25-dihydroxyvitamin D3 has been proven to be able to control the formation and biomineralization of tissue through a regulatory gene. A previous research even showed that a cell responsible for the formation of the enamel (ameloblasts), dentin (odontoblasts) and bone (osteoblasts, osteoclasts) was the target of  1,25-dihydroxivitamin D3. Purpose: This research was aimed to determine the role of 1,25- dihydroxyvitamin D3 in vivo in the development of teeth and alveolar bone tissue by analyzing MSX2 gene expression as a gene marker responsible for the growth and development of enamel, dentin, tooth root and alveolar bone. Methods: Samples used for RT-PCR analysis were total RNA of insisivus teeth and alveolar bone derived from mice. RT-PCR analysis was conducted by using primer-specific gene, MSX2. Primer gene, GAPDH, was also used as an internal control. Five hundred nanograms of total RNA were used as a template for PCR. Semi quantitative results of PCR were quantified by using ImageJ software. Results: RT-PCR analysis showed that the expression level of MSX2 was enhanced in the samples of teeth and alveolar bone treated with 1,25 dihydroxyvitamin D3. The increasing of MSX2 expression significantly occurred in alveolar bone samples. Conclusion: It can be concluded that 1,25 dihydroxyvitamin D3 could enhance MSX2 expression as a marker of the development of teeth and alveolar bone tissue. Therefore, 1,25-D3 dihydroxyvitamin is expected to be used as an agent to help the regeneration of teeth and bone tissue.